ANALISIS DAN PERBANDINGAN PENGGUNAAN LTSP PADA JARINGAN KOMPUTASI KLIEN SERVER SEBAGAI PRIVATE CLOUD DENGAN JARINGAN KOMPUTASI KLIEN SERVER KONVENSIONAL - Rauf Fauzan (Jurnal Teknologi dan Informasi (JATI), 2015)
This research makes client-server system with LTSP. LTSP offers solutions and alternatives for the network infrastructure of computing that are still using conventional methods. LTSP provides a solution in the shape of thin-client as the client so that the price to build this system is a lot more inexpensive. The intent of this research so that slowly the system/agency will change over to using the LTSP network infrastructure as the foundation for their computing infrastructure system.The method of research conducted to establish this system is to do simulations and comparisons. Simulation of LTSP and then compare the results with the network client-server computing. On that point are four faces to get a benchmark comparison, namely: cost, time, care, and protection.From the effects of the research, the authors found that the build system with LTSP method has advantages compared to using conventional methods. LTSP using thin-client as the client so that the price is a lot more inexpensive. LTSP uses only a single server, which means the treatment is done only on a single computer. Suggestion system development is how in the future this system is capable to handle fat-client and client-hybrid, and was able to completely replace the conventional client-server model.